2011
DOI: 10.1097/01.aoa.0000393150.38252.ef
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Internal Versus External Tocodynamometry for Monitoring Labor

Abstract: BackgroundIt has been hypothesized that internal tocodynamometry, as compared with external monitoring, may provide a more accurate assessment of contractions and thus improve the ability to adjust the dose of oxytocin effectively, resulting in fewer operative deliveries and less fetal distress. However, few data are available to test this hypothesis. MethodsWe performed a randomized, controlled trial in six hospitals in the Netherlands to compare internal tocodynamometry with external monitoring of uterine ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…Studies have demonstrated that the use of IUPTs had no advantage when compared to noninvasive means of assessing uterine contractility during labor. [72][73][74] In addition, IUPT readings may depend on patient position, or on their location within the uterus and, most importantly, they do not correlate well with progress in cervical dilatation 70,75 or with the need for cesarean delivery. 69 Normal progress in dilatation is achieved over a broad range of uterine activity, and the pattern of contractions may be as important as their strength.…”
Section: Analytical Issuesmentioning
confidence: 99%
“…Studies have demonstrated that the use of IUPTs had no advantage when compared to noninvasive means of assessing uterine contractility during labor. [72][73][74] In addition, IUPT readings may depend on patient position, or on their location within the uterus and, most importantly, they do not correlate well with progress in cervical dilatation 70,75 or with the need for cesarean delivery. 69 Normal progress in dilatation is achieved over a broad range of uterine activity, and the pattern of contractions may be as important as their strength.…”
Section: Analytical Issuesmentioning
confidence: 99%
“…uterine activity. Nevertheless, unlike external monitoring [2,4,10,11,26,12], internal monitoring requires membrane rupture and it has not showed significant improvement on the outcome of difficult births, which is of major concern in obstetrics. Moreover, intra-amniotic pressure is only an indirect assessment of the uterine activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a high frequency of women had vaginal births with uterine activity less than 200 MVUs. 20,22 Importantly, an increased fallto-rise ratio was associated with increased incidence of cesarean birth. 15,17,18 Similarly, increased EMG power density spectrum peak frequency 10,13 and increased sample entropy of the EMG signal were associated with cesarean birth.…”
Section: Discussionmentioning
confidence: 98%
“…In the parent study, the same research group reported that titration of oxytocin augmentation to uterine activity greater than 200 MVUs did not reduce the incidence of cesarean birth or adverse neonatal outcomes compared with titration to 3 to 4 contractions per 10 minutes measured by tocodynamometry. 22 In summary, lower MVU values are associated with cesarean birth; however, because of low predictive value for cesarean birth and high frequency of women with MVUs less than 200 who have a vaginal birth, uterine activity less than 200 MVUs may not be an appropriate criterion for the diagnosis of labor dystocia. Intrauterine pressure measured at single time points is not likely to identify uterine fatigue specifically as intrauterine pressure is expected to be reduced in both fatigue and understimulation of uterine contractions.…”
Section: Uterine Activity Measured By Montevideo Unitsmentioning
confidence: 98%